Partisipasi Masyarakat dalam Pembayaran Pajak Bumi dan Bangunan Di Desa Kota Raja dan Desa Ujung Murung Kecamatan Amuntai Selatan Kabupaten Hulu Sungai Utara - Erwin Maulana (Program Magister Ilmu Administrasi Bisnis FISIP Universitas Lambung Mangkurat, 2025)
Abstract: In South Amuntai District, community participation in paying land and building tax is still low due to phenomena such as a lack of information provision in the form of outreach, light sanctions for taxpayers, no ball pick-up method in collecting land and building tax, no officers stipulation of PBB in conducting door to door data collection on tax objects and tax subjects. This study aims to determine community participation in payments and the factors that influence community participation in PBB payments. This research uses a qualitative approach with a qualitative descriptive type. Data collection techniques used are interviews, observation, and documentation. Sources of data were taken through the withdrawal of informants by purposive sampling totaling 16 people. After the data is collected, it is then analyzed using techniques including data reduction, data presentation and drawing conclusions. In seeking the validity of the data, a credibility test was made by extending observations, increasing persistence, triangulation, peer discussions, negative case analysis and member checking. The results of this study indicate that community participation in paying land and building taxes is not good. It can be seen from: First, information is still not good enough because there is still a lack of information. Second, the attitude is still not good because awareness is still lacking. Third, the economic level is still not good because the key taxpayer's income comes from a desire to participate. Fourth, interaction and communication is still lacking, interaction from agencies and communication to direct taxpayers. While what is quite good can be seen from: First, the opportunity to participate is quite good because the agency has provided opportunities for taxpayers to participate. Second, the perception of the program is still quite good, it can be seen from the perception of taxpayers that there are still many taxpayers who think it is not too important to pay. Factors that influence community participation are: lack of information provision, community economic level, lack of public awareness, lack of interaction from related agencies. Suggestions to the Head of the North Hulu Sungai Regency Regional Revenue Agency, especially to the Head of PBB to further increase socialization activities by inviting taxpayers and providing information through various forms such as banners, radio, TV, social media and others. To the Village Head and Village Apparatus provide collection services directly to homes and preferably also village officials who go directly to the community and hold village meetings regarding land and building tax awhich invites some taxpayers. To the public to be more concerned with land and building taxes that this tax must be paid because the tax funds will also be for the benefit of the community as well